Do School Alma Mater Ties Between Engagement and Review Partners Threaten Audit Firm Quality Control? Evidence from Audit Adjustments - Sharma, Divesh S.; Wu, Liansheng; Xing, Qiuhang (The Accounting Review, 2026)
ABSTRACT Although audit regulators worldwide concur that the rigor of audit firms’ internal engagement quality reviews (EQRs) is paramount to an audit firm’s audit quality, they are concerned that relationships between audit engagement partner (AEP) and engagement review partner (ERP) working in the same firm can undermine these reviews. We utilize confidential proprietary ERP and audit adjustment data to investigate how school alma mater ties between AEPs and ERPs affect audit adjustments in China. Our results reveal that audit adjustments are significantly lower when an AEP and ERP share school ties. This effect is more pronounced when the ERP is less competent than and lacks authority over the AEP, when the ERP and AEP perform mutual reviews or previously coaudited a client, and when the AEP’s work is flawed. Finally, semistructured partner interviews corroborate our empirical findings and strengthen our practical and policy implications. Data Availability: These proprietary data were provided to us with the understanding that it would be used only for independent academic research. Our research team is obligated under nondisclosure and confidentiality conditions to not disclose or share the confidential information which includes all of the data received from the data providers of the Chinese government and not to report information in any article or presentation that would inadvertently reveal (including any potential link) the identity of the partners, firms, their characteristics, and the audit adjustment data. No other restrictions were imposed by the data providers regarding the use of the data purely for academic research purposes and in communicating the research findings. Other data not subject to this confidentiality nondisclosure are available from sources identified in the text. JEL Classifications: M40; M41; M42.